Effect Of Roselle Petal Extract On Decreased Levels Of Mda In Rats With Type 2 Diabetes - Novera Herdiani; Edza Aria Wikurendra (Jurnal Ilmiah Kesehatan, 2021)
Introduction: Diabetes mellitus type 2 is a metabolic disorder, namely a decrease in peripheral tissues' response to insulin. Free radicals increase, which results in the forming of Malondialdehyde (MDA). Roselle flower petals is an antioxidant to reduce free radical damage. Purpose: This study aims to analyze the effect of roselle petal extract on decreased MDA levels in mice induced by diabetes. Method: The rats were divided into four treatments group as follow: 1) control negative, 2) control positive, 3) treatment dose I (administering roselle petal extract 195 mg/200 gram body weight), 4) treatment dose II (giving roselle petal extract 260mg/ 200 gram body weight). MDA levels were measured using Thiobarbituric acid (TBA) assay. Result: There was an effect of rosella petal extract in the group with 260 mg/200 of rosella petal extract (p=0.005) and 195 mg/200 of rosella petal extract (p=0.041) compared with the positive control group. Conclusion: rosella petal extract significantly reduces MDA levels in rats induced by type 2 diabetes.